Photonic crystal bio sensor / Mohd Arif Mohd Ghani - Mohd Ghani, Mohd Arif (2010)
The objective of this project is to investigate the suitability of a photonic crystal for detection dengue infected blood. In sensor application; photonic crystal is a periodic structure of materials with differing refractive indices. This paper presents the simulation of photonic crystal bio sensor for detection dengue infected blood. The project involved designing photonic crystal bio sensor. Finite Different Time Domain (FDTD) is used to stimulate reflection and transmission characteristic over range of wavelength. Band diagram of photonic crystal bio sensor is also calculated. The work presented here shows that the photonic crystal bio sensor is suitable for measuring dengue infected blood. This can be proved by the blue shift observed in the graph.